New public governance, the third sector and co-production - Pestoff, Victor Alexis; Brandsen, Taco; Verschuere, Bram, 1977- (Routledge critical studies in public management ;, 2012)
In recent years public management research in a variety of disciplines has paid increasing attention to the role of citizens and the third sector in the provision of public services. Several of these efforts have employed the concept of co-production to better understand and explain this trend. This book aims to go further by systematizing the growing body of academic papers and reports that focus on various aspects of co-production and its potential contribution to new public governance. It has an interdisciplinary focus that makes a.